Students' Interest in Using Digital Books in General Biology Courses at Higher Education Institutions in the Era of Society 5.0 - Zikra, Zikra; Lufri, Lufri; Andromeda, Andromeda; Mufit, Fatni; Fitri Arsih (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
The rapid growth of digital technology in higher education has transformed the provision of learning resources and increased the relevance of digital books as instructional media. However, empirical studies on students’ interest in using digital books in Indonesian higher education, particularly in General Biology courses, remain limited. This study aimed to describe students’ interest in digital books as learning resources in a General Biology course. A descriptive quantitative survey design was employed involving 97 students from the Biology Education Study Program at Universitas PGRI Sumatera Barat, Indonesia, across three academic year cohorts: 2023, 2024, and 2025. Data were collected using a validated 25-item questionnaire based on a four-point Likert scale. The questionnaire measured five dimensions of student interest: Interest, Enjoyment, Desire, Learning Motivation, and Attitude toward Technology. Data were analyzed descriptively using mean scores and categorical interpretation. The findings showed that students had a high level of interest in digital books across all dimensions, with an overall mean score of 3.03 on a four-point scale. The highest mean score was found in Attitude toward Technology (3.10), followed by Interest (3.06), Enjoyment (3.05), Learning Motivation (3.02), and Desire (2.91). The 2023 cohort showed the most favorable interest profile, while the 2024 cohort experienced a slight decline and the 2025 cohort showed partial improvement. These findings indicate that digital books are positively received by General Biology students and can be strategically integrated into higher education learning environments.